Commemorative Issue in Honor of Professor María Vallet Regí: 20 Years of Silica-Based Mesoporous Materials - Montserrat Colilla; Isabel Izquierdo-Barba; Gloria P. Rodríguez-Donoso; Natalia Otamendi-Vallet (MDPI AG, 2022)
This Special Issue entitled "Commemorative Issue in Honor of Professor María Vallet-Regí: 20 Years of Silica-Based Mesoporous Materials" arises from the initiative of the editorial team of Pharmaceutics to pay homage to Professor Maria Vallet-Regí for her ground-breaking pioneering scientific contribution to the field of silica-based mesoporous materials for biomedical applications [...]